2020
DOI: 10.3390/su12020740
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Action as a Driving Force of Change. The Meninas of Canido, Art in the Street as an Urban Dynamizer

Abstract: The austerity policies imposed by the government in the wake of the 2007 crisis have deteriorated the welfare state and limited neighborhood recovery. Considering the inability and inefficiency on the part of administrations to carry out improvement actions in neighborhoods, it is the neighborhood action itself that has carried out a series of resilient social innovations to reverse the dynamics. In this article, we will analyze the Canido neighborhood in Ferrol, a city in north-western Spain. Canido is tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Thus, media can highlight its contribution when street art brings positive effects in some territories or is used as an alarm signal for certain spaces (abandoned, deteriorated, squatted, etc.). The involvement of the population is essential through actions of support and participatory involvement, being able to become a way of citizen action for urban change [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, media can highlight its contribution when street art brings positive effects in some territories or is used as an alarm signal for certain spaces (abandoned, deteriorated, squatted, etc.). The involvement of the population is essential through actions of support and participatory involvement, being able to become a way of citizen action for urban change [6].…”
Section: Discussionmentioning
confidence: 99%
“…Burkner and Totelecan [54] demonstrated that it is not possible to verify the correlation between murals and increasing of residential market values in the real estate market in a district from Naples, but agreed that it has an impact on the social and physical sustainability of the place. Other authors focused, too, on their research on the sense of place and social capital [6].…”
Section: Case Study-bucharest City Center and The Context For Street ...mentioning
confidence: 99%
See 2 more Smart Citations